Sodium dodecyl sulfate/β-cyclodextrin vesicles embedded in chitosan gel for insulin delivery with pH-selective release - Zhuo Li; Haiyan Li; Caifen Wang; Jianghui Xu; Vikramjeet Singh; Dawei Chen; Jiwen Zhang (Elsevier, 2016)
In an answer to the challenge of enzymatic instability and low oral bioavailability of proteins/peptides, a new type of drug-delivery vesicle has been developed. The preparation, based on sodium dodecyl sulfate (SDS) and β-cyclodextrin (β-CD) embedded in chitosan gel, was used to successfully deliver the model drug-insulin. The self-assembled SDS/β-CD vesicles were prepared and characterized by particle size, zeta potential, appearance, microscopic morphology and entrapment efficiency. In addition, both the interaction of insulin with vesicles and the stability of insulin loaded in vesicles in the presence of pepsin were investigated. The vesicles were crosslinked into thermo-sensitive chitosan/β-glycerol phosphate solution for an in-situ gel to enhance the dilution stability. The in vitro release characteristics of insulin from gels in media at different pH values were investigated. The insulin loaded vesicles-chitosan hydrogel (IVG) improved the dilution stability of the vesicles and provided pH-selective sustained release compared with insulin solution-chitosan hydrogel (ISG). In vitro, IVG exhibited slow release in acidic solution and relatively quick release in neutral solutions to provide drug efficacy. In simulated digestive fluid, IVG showed better sustained release and insulin protection properties compared with ISG. Thus IVG might improve the stability of insulin during its transport in vivo and contribute to the bioavailability and therapeutic effect of insulin.